Use of a digital tool as a professional development resource to improve oral communicative competence of children in primary and secondary education - Gràcia, Marta; Jarque, Maria Josep; Riba, Carles; Vega, Fàtima (Revista de Investigación en Logopedia, 2020)
The school is a natural context in which the communication strategies of teachers in their interaction with students are essential for the development of their oral competence. The goal of the study is to contribute to the improvement of teaching practice in relation to communicative and oral language competence through the use of a digital tool. The participants were 8 teachers and their pupils from 6 kindergarten and primary schools in Catalonia, 5 of which are public (2 ordinary and 3 cyclical) and 1 is private (special). As for teachers, 4 constitute the intervention group and 4, the comparison group. For 6 months, the 4 teachers of the intervention groups used the tool to self-evaluate their practices, made decisions to improve it and to introduce changes. The researchers observed 5 class sessions of each teacher, evaluated them with the same tool and each teacher-researcher pair talked and reflected on the classes in 5 meetings during the semester. The evaluations of the class sessions yielded significant differences between the scores obtained by the teachers who participated in the professional development process and those who did not. We argue, therefore, that the digital tool has contributed to the professional development of teachers and to the improvement of the oral communicative competence of their students. The implications derived from this research highlight the need to train teachers in the area of teaching the communicative and linguistic competence of students with the help of digital technology.
Keywords: self-assessment; communicative competence; language teaching; assessment; oral language